2016
DOI: 10.3389/fpls.2016.00501
|View full text |Cite
|
Sign up to set email alerts
|

Heat Priming Induces Trans-generational Tolerance to High Temperature Stress in Wheat

Abstract: Wheat plants are very sensitive to high temperature stress during grain filling. Effects of heat priming applied to the first generation on tolerance of the successive generation to post-anthesis high temperature stress were investigated. Compared with the progeny of non-heat primed plants (NH), the progeny of heat-primed plants (PH) possessed higher grain yield, leaf photosynthesis and activities of antioxidant enzymes and lower cell membrane damage under high temperature stress. In the transcriptome profile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 76 publications
(86 reference statements)
4
67
0
4
Order By: Relevance
“…So far, transcriptome and proteome profiles have been investigated in wheat under heat stress, revealing differences in gene expression and protein levels, respectively (Liu et al , 2015; Ahammed and Yu, 2016; Wang et al , 2016 b ; Zhang et al, 2016, 2017; Lu et al , 2017). However, protein post-translational modifications (PTMs) are linked with plant stresses, and reversible protein phosphorylation in particular functions as a crucial regulatory mechanism in many biological processes (Hashiguchi and Komatsu, 2016), including the regulation of abiotic stress signalling in crops (Kline et al , 2010; Bonhomme et al , 2012; Nguyen et al , 2012; Yang et al , 2013; Zhang et al , 2014a, b; Ahammed and Yu, 2016; Zhen et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…So far, transcriptome and proteome profiles have been investigated in wheat under heat stress, revealing differences in gene expression and protein levels, respectively (Liu et al , 2015; Ahammed and Yu, 2016; Wang et al , 2016 b ; Zhang et al, 2016, 2017; Lu et al , 2017). However, protein post-translational modifications (PTMs) are linked with plant stresses, and reversible protein phosphorylation in particular functions as a crucial regulatory mechanism in many biological processes (Hashiguchi and Komatsu, 2016), including the regulation of abiotic stress signalling in crops (Kline et al , 2010; Bonhomme et al , 2012; Nguyen et al , 2012; Yang et al , 2013; Zhang et al , 2014a, b; Ahammed and Yu, 2016; Zhen et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…If scientists were able to sequence part of a species' genome, or even perhaps all of it, then we could potentially determine whether there is a gene for temperature tolerance. This has already been done in species like wheat where research has shown that there has been an enhanced temperature tolerance due to gene expression (Wang, 2016). These genes have been linked to the production of ABA, cytokinin and auxin signaling transduction pathways.…”
Section: Macroalgal Physiological Researchmentioning
confidence: 99%
“…So far, transcriptome and proteome profiles were investigated in wheat under heat stress, revealing differences in gene expression and protein levels, respectively (Liu et al , 2015; Wang et al , 2016; Zhang et al , 2017). Often, changes in gene expression for enzymes were in line with changes in the metabolite profiles upon stress (Rizhsky, 2004).…”
Section: Introductionmentioning
confidence: 99%